2018
DOI: 10.1007/s10346-018-0986-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of automatic landslide mapping: numerical experiments towards the best solution

Abstract: The automatic detection of landslides after major events is a crucial issue for public agencies to support disaster response. Pixel-based approaches (PBAs) are widely used in the literature for various applications. However, the accuracy of PBAs in the case of automatic landslide mapping (ALM) is affected by several issues. In this study, we investigated the sensitivity of ALM using PBA through digital terrain models (DTMs). The analysis, carried out in a study area of Poland, consisted of the following steps:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 54 publications
7
53
0
Order By: Relevance
“…We successfully applied and assessed an automated open source landslide detection procedure solely based on HRDTM-derived data. The moderate classification agreement based on the pixel-level assessment (κ of 0.42, and 0.48 in post-processed classification) is consistent with previous research using similar methods [13,15] (κ between 0.45 and 0.6). Although different performance measures and data sets were used in studies within commercial software, they also showed a moderate predictive skill [7,18] (percentage of inventoried landslides detected correctly at the object level 69%, after post-processing 66%; 71% in [7] and 68.7% and 73.3% in [18]).…”
Section: Classification Accuracy and Relevant Predictorssupporting
confidence: 89%
See 4 more Smart Citations
“…We successfully applied and assessed an automated open source landslide detection procedure solely based on HRDTM-derived data. The moderate classification agreement based on the pixel-level assessment (κ of 0.42, and 0.48 in post-processed classification) is consistent with previous research using similar methods [13,15] (κ between 0.45 and 0.6). Although different performance measures and data sets were used in studies within commercial software, they also showed a moderate predictive skill [7,18] (percentage of inventoried landslides detected correctly at the object level 69%, after post-processing 66%; 71% in [7] and 68.7% and 73.3% in [18]).…”
Section: Classification Accuracy and Relevant Predictorssupporting
confidence: 89%
“…For landslide classification we used the support vector machine, a flexible supervised machine-learning technique [56]. SVM has become a widely used classification method that has shown its potential in landslide distribution modeling [7,13,21]. We used the e1071 package in R [57] within the mlr modeling framework.…”
Section: Classification and Variable Importancementioning
confidence: 99%
See 3 more Smart Citations